2018
DOI: 10.1016/j.ecolind.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Brain as a target organ of climate events: Environmental induced biochemical changes in three marine fish species

Abstract: The present study aims to examine physiological and biochemical response of three commercial fish species (Dicentrarchus labrax; Platichthys flesus and Solea solea), over contrasting environmental dynamics: an extremely dry (2012) and flood (2014) years, in a shallow temperate southern European estuary, the Mondego Estuary (Portugal). Physiological and biochemical biomarkers were evaluated by a principal component analysis (PCA), which allowed to conclude that severe climatic events affected the set of fish sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The upregulated expression of many genes encoding selenoproteins and the thiol oxidoreductase family in the present study suggests that increasing day length increases oxidative stress in the salmon brain, and that this change in gene expression protected it from oxidative damage. Studies have suggested that the brain is a good indicator of oxidative stress in aquatic organisms facing a plethora of environmental changes [ 69 ]. However, to the best of our knowledge, our study is the first to indicate that seasonally varying photoperiods directly influence salmon brain redox balance.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated expression of many genes encoding selenoproteins and the thiol oxidoreductase family in the present study suggests that increasing day length increases oxidative stress in the salmon brain, and that this change in gene expression protected it from oxidative damage. Studies have suggested that the brain is a good indicator of oxidative stress in aquatic organisms facing a plethora of environmental changes [ 69 ]. However, to the best of our knowledge, our study is the first to indicate that seasonally varying photoperiods directly influence salmon brain redox balance.…”
Section: Discussionmentioning
confidence: 99%